A pivotal shift: Europe's strategic partnerships and rebalance to East Asia. (2nd January 2019) - Kim, Jangho; Richey, Mason; Han, Sukhee
ABSTRACT: This article addresses how two globally critical regions – Europe and East Asia (especially Northeast Asia) – are transforming their relationship as an international system defined by multipolarity emerges from the unraveling of the liberal international order. This transformation includes increased trade, developing strategic partnerships between the EU and selected East Asian states, nascent EU-ASEAN inter-regional cooperation, and more diplomatic through-put among East Asian states and their EU and member state counterparts. This article examines the question of how Europe is performing its own 'pivot/rebalance' to East Asia (specifically Northeast Asia) in terms of trade, diplomacy, and security. In turn, the question arises as to how receptive East Asian states have been to this European overture. First we cover the path of how we have arrived at the historical juncture in which the EU is 'pivoting/rebalancing' to East Asia (specifically Northeast Asia).